2020
DOI: 10.5049/ebp.2020.18.2.44
|View full text |Cite
|
Sign up to set email alerts
|

Liver Infarction and Venous Thromboembolism after Tamoxifen Use in an ADPKD Patient with Encapsulating Peritoneal Sclerosis: A Case Report

Abstract: Encapsulating peritoneal sclerosis (EPS) is a potentially fatal complication after long-term peritoneal dialysis, and tamoxifen can be used for its prevention and treatment. However, tamoxifen is known to increase the risk of venous thromboembolism. A 49-year-old woman was admitted with sudden abdominal pain. The patient had received peritoneal dialysis for 20 years and switched to hemodialysis after the diagnosis of EPS. Tamoxifen (10 mg) and prednisolone (20 mg) had been administered for 8 months. On compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In addition, encapsulated peritoneal sclerosis (EPS) is a potentially fatal complication after prolonged peritoneal dialysis for which tamoxifen may be used for prevention and treatment. However, it has been reported that ADPKD patients with EPS may be at risk of hepatic infarction and venous thromboembolism after treatment with tamoxifen [ 65 ].…”
Section: Clinical Manifestations Of Vascular Lesionsmentioning
confidence: 99%
“…In addition, encapsulated peritoneal sclerosis (EPS) is a potentially fatal complication after prolonged peritoneal dialysis for which tamoxifen may be used for prevention and treatment. However, it has been reported that ADPKD patients with EPS may be at risk of hepatic infarction and venous thromboembolism after treatment with tamoxifen [ 65 ].…”
Section: Clinical Manifestations Of Vascular Lesionsmentioning
confidence: 99%